The Effect of Lavender Oil on Perioperative Pain, Anxiety, Depression, and Sleep after Microvascular Breast Reconstruction: A Prospective, Single-Blinded, Randomized, Controlled Trial - Shammas, Ronnie L.; Marks, Caitlin E.; Broadwater, Gloria; Le, Elliot; Glener, Adam D.; Sergesketter, Amanda R.; Cason, Roger W.; Rezak, Kristen M.; Phillips, Brett T.; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2021)
Background Psychosocial distress, depression, or anxiety can occur in up to 50% of women after a breast cancer diagnosis and mastectomy. The purpose of this study was to assess the potential benefit of lavender oil as a perioperative adjunct to improve anxiety, depression, pain, and sleep in women undergoing microvascular breast reconstruction.Methods This was a prospective, single-blinded, randomized, controlled trial of 49 patients undergoing microvascular breast reconstruction. Patients were randomized to receive lavender oil or placebo (coconut oil) throughout their hospitalization. The effect of lavender oil on perioperative stress, anxiety, depression, sleep, and pain was measured using the hospital anxiety and depression scale, Richards–Campbell Sleep Questionnaire, and the visual analogue scale.Results Twenty-seven patients were assigned to the lavender group and 22 patients were assigned to the control group. No significant differences were seen in the perioperative setting between the groups with regard to anxiety (p = 0.82), depression (p = 0.21), sleep (p = 0.86), or pain (p = 0.30) scores. No adverse events (i.e., allergic reaction) were captured, and no significant differences in surgery-related complications were observed. When evaluating the entire cohort, postoperative anxiety scores were significantly lower than preoperative scores (p < 0.001), while depression scores were significantly higher postoperatively as compared with preoperatively (p = 0.005).Conclusion In the setting of microvascular breast reconstruction, lavender oil and aromatherapy had no significant adverse events or complications; however, there were no measurable advantages pertaining to metrics of depression, anxiety, sleep, or pain as compared with the control group.
Keywords: breast reconstruction; aromatherapy; reconstruction; breast cancer; lavender